Translation and validation of the Nursing Outcomes Classification labels and definitions for acute care nursing in Iceland - Gudmundsdottir, Elisabet; Delaney, Connie; Thoroddsen, Asta; Karlsson, Thorlakur (Journal of Advanced Nursing, 2004)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field BACKGROUND: The Nursing Outcomes Classification (NOC), second edition, consists of 260 patient outcomes with definitions. This has been translated into five languages, but has not been clinically validated outside the United States of America (USA). AIM: The aim of this paper is to describe the translation of the labels and definitions from the NOC, second edition from English to Icelandic and validation for acute-care nursing in Iceland. METHOD: A survey that has been designed to identify nurses' perception of the percentage of patients' for whom each NOC outcome is relevant in clinical nursing practice was used for clinical validation in this study. The translation procedure involved source to target language translation, parallel comparison, pilot test and field test. Validation included test-retest to measure the reliability for each of the 260 outcome variables. Data collected from 140 clinical nurses from 54 departments within 13 nursing specialties at Landspitali University-Hospital in Iceland, in November 2001, were analysed to establish construct validity by confirmatory factor analysis. Internal consistency was calculated. RESULTS: Translation was successful. Test-retest showed that 181 of the 260 NOC outcomes were significant (P < 0.05) and moderately or highly correlated (r > 0.50) (Pearson's correlation). The confirmatory factor analysis showed that 22 of the 29 NOC classes had only one factor at the loading criteria > or =0.30. Of the 260 outcomes, 244 had loading on one factor (> or =0.30) within its class. Internal consistency was >0.80 (Cronbach's alpha). LIMITATIONS: Low response rate was a limitation. The indicators of each NOC outcome were not addressed. CONCLUSION: The Icelandic version of the NOC survey is a comprehensive tool that can be applied to nursing in acute-care for research purposes as well as to prepare for the implementation of NOC in clinical ...